Secondary electron emission properties of Zn-doped MgO thin films grown via electron-beam evaporation - Yu, Hak Ki (Thin Solid Films, 2018)
The secondary electron emission (SEE) properties of Zn-doped MgO thin films (~700 nm thickness) grown via electron-beam evaporation have been studied based on Paschen curve measurements. The Zn-doped (1 at.%) MgO film shows an improved SEE coefficient (γ) compared to that of non-doped MgO from 0.02 to 0.05 in the 100 V Pa−1 m−1 region. The origin of a superior γ is due to the reduction in the band-gap from 6.79 eV to 6.26 eV (the values are measured via ultra-violet photoemission spectroscopy; UPS) because γ is normally determined by the Auger neutralization process, which uses the neutralization energy of ion valence band electron emission. This thin film can be used in new kinds of plasma devices, such as flat-fluorescent lamps, plasma displays, electron emitters, and ionized mass spectrometers.
Keywords: Auger neutralization; Electron beam evaporation; Electron emitters; Flat fluorescent lamp; Paschen curves; Secondary electron emissions; Valence-band electrons; Zinc doped; Electron-beam evaporation; Paschen curve; Secondary electron emission; Zinc-doped magnesium oxide